The Transformation of Zakat in Promoting the Growth of the Halal Industry in Indonesia - Hak, Nurul; Susilawati, Nilda; Novriadi, Dedy (Journal of Ecohumanism, 2024)
Indonesia holds significant potential for developing halal products due to its status as the country with the largest Muslim population in the world. This has driven the availability of halal products as societal awareness of consuming halal goods continues to rise. However, this potential is not fully supported by the community's capability to act as suppliers of halal products due to limited financial support. Zakat, as a source of social finance, can contribute to the growth and sustainability of the halal industry. This study employs a qualitative descriptive method by reviewing articles related to zakat and its contributions to the development of the halal industry. The results show that zakat plays various roles in contributing to the growth and sustainability of the halal industry, including in social welfare and poverty alleviation, consumer trust and confidence, investment in education and skill development, support for micro, small, and medium enterprises (MSMEs), infrastructure development, and the promotion of ethical business practices.